The Analysis of Active Bribery in Positive Criminal Law of Germany and Austria - Mijo Galiot (LeXonomica, 2017)
The criminal policy of preventing the commission of crimes, especially corruption and bribery, is of great importance for every regulated legal system. The success of the named policy depends largely on the overall political and economic development of each country. In support of the existing scientific debate, this paper analyses the positive criminal law regulation of the Federal Republic of Germany and the Republic of Austria with regard to the question of active bribery as one of the main forms of corrupt behaviour. The author will comparatively present the German and Austrian criminal systems, which, same as the Croatian, belong to European continental criminal legal system, and will thus address the fundamental similarities and differences between the legal regulations of active bribery within the named legislations.